IMPACT ASSESSMENT OF KONANKI WATERSHED PROJECT IN PRAKASAM DISTRICT ON BIO-PHYSICAL, ENVIRONMENTAL AND SOCIO-ECONOMIC ASPECTS - P. RANJIT BASHA, M. SIVA PRASAD, B. VENKATESULU NAIK, R. INIGO ARUL SELVAN; L. SUDHAKARA REDDY* (The Journal of Research ANGRAU, 2019)
Konanki mega watershed project was sanctioned in the year 2010-11 and implemented in Prakasam district till March 2018. Impact study was conducted on environmental and socio-economic indicators by physical visit to the project area and through bio-physical measurable characteristics by remote sensing and GIS techniques to assess the outcomes and impact on the watershed community. The total geographical area of the project is 10,574 ha having undulating terrain with net treatable area of 4,773 ha encompassing seven micro watersheds. The impact of watershed management interventions were observed in terms of sustaining the productivity of crops under drought conditions, development of waste lands and current fallow lands, increase in cultivated area, improvement in agrivegetation and vigour, expansion of water bodies, soil moisture in the profile as a result of the effective in-situ soil conservation and water conservation activities, increase in milk productivity,etc. The water productivity also found improved through conservation measures and judicious use of available water resources. Watershed interventions helped in enhancement of family income especially ofthe marginal farmers (37.1 % rise), small farmers (15% rise) and landless poor (76.1% rise) of watershed community.